Pancreaticojejunostomy versus pancreaticogastrostomy after pancreaticoduodenectomy to prevent post-operative pancreatic fi stula, a dissonance between evidence and practice - Noman Shahzad; Tabish Umer Chawla; Saleema Begum; Fareed Ahmed Shaikh (Archives of Clinical Gastroenterology - Peertechz Publications, 2018)
Leakage of pancreatic enzymes leading to either formation of abdominal collection or pancreatic fi stula is one the most feared complications after pancreaticoduodenectomy. Owing to high morbidity and cost related to pancreatic fi stula, multiple interventions including various types of pancreaticoenteric anastomosis have been proposed to prevent this complication. Despite some randomized controlled trials and meta-analyses favoring pancreaticogastrostomy over pancreaticojejunostomy, clinical practice has not witnessed any change in preference of individual surgeons. One of the underlying facts is that there are various ways of doing pancreatic anastomosis and trials have compared only specifi c techniques while a few novel techniques that have been reported to have very low pancreatic fi stula risk have never been compared in randomized controlled trials comparing pancreaticogastrostomy versus pancreaticojejunostomy. Moreover individual surgeons' comfort and training also matters, and in many instances same results are not reproduced as reported for primary center where technique was developed. So though a good number of randomized controlled trials have been conducted to compare pancreaticogastrostomy with pancreaticojejunostomy, variations in techniques of performing anastomosis limit external validity as well as pooling the data for meta-analysis. Furthermore subgroup of patients with soft pancreas, who are at high risk of pancreatic leak, should be looked at separately for potential benefi t of type of pancreatic anastomosis.